Histology, histochemistry and ultrastructure of the nasopharyngeal tonsil of the buffalo (Bubalus bubalis). (7th June 2019) - Girgiri, Ibrahim Alhaji; Kumar, Pawan
Abstract: The light microscopic appearance and ultrastructure of the nasopharyngeal tonsil (tonsilla pharyngea), collected from 12 adult buffaloes of local mixed breed, were explored for the distribution of different types of epithelia, lymphoid tissue and high endothelial venules. The tonsillar mucosa was lined by pseudostratified columnar ciliated epithelium having goblet cells. The respiratory epithelium associated with the underlying lymphoid tissue formed the lymphoepithelium. The epithelium was further modified into follicle‐associated epithelium (FAE) characterized by reduced epithelial height, presence of a few dome‐shaped cuboidal cells equivalent of the M‐cells and absence of goblet and ciliated cells. The lymphoid tissue was distributed in the form of isolated lymphoid cells, diffuse lymphoid tissue and lymphoid follicles, mainly distributed within the propria‐submucosa along with the sero‐mucous glandular tissue. The goblet cells of the respiratory epithelium and the acinar cells contained different mucopolysaccharides. Scanning electron microscopy of the surface mucosa demonstrated a dense mat of cilia, island‐like arrangement of microvillus cells, M‐cells and a few brush‐like cells. The transmission electron microscopy revealed the different cell organelles of the respiratory epithelium and the FAE. Lymphocyte migration via the high endothelial venules in the propria‐submucosa was also observed.